Analisis Faktor Kesulitan Membaca Peserta Didik Pada Jenjang Sekolah Menengah Pertama Kelas VI Serta Upaya Mengatasinya - Vebiana Anugrah Rezni; Safitri , Sani (Jurnal Penelitian dan Pendidikan IPS, 2023)
The aim of this research is to describe the difficulties faced by Grade 7 students in junior high schools which hinder their initial reading learning. This research includes observational research. Data collection techniques use observation, interviews and documentation. The data obtained was analyzed descriptively after first being reduced (data reduction), and its validity was tested through a data credibility test. The results of the research show that the forms of difficulties faced by grade 7 students at the Junior High School where the researcher works in the campus teaching program which have the potential to hinder students' learning to read are as follows: 1) students find it difficult to pronounce letters that have the same sound as j with g, students have difficulty reading words with more than 4 letters, students cannot read words well, students have difficulty spelling the instructed syllables, students have difficulty distinguishing between the letters b and d, the letters m and w, and the letters j with g and so on, 2) factors that hinder students from helping Class 7 students read are intellectual factors, environmental factors such as parents, psychological factors, and the Covid-19 pandemic factor. The solution to this problem is that students are given additional hours outside of class, such as by creating a literacy class that meets twice a week and then collaborates according to the students' abilities.